Modelling of prevailing water distribution network in Putrajaya, Malaysia - Mohamad, Nur Diyana; Ash'aari, Zulfa Hanan (Centre for Environmental Sustainability and Water Security (IPASA), Universiti Teknologi Malaysia, 2019)
Water is a basic need for every human being, which is used for numerous activities such as drinking, cleaning, sanitation, etc. This indicates the fact that how vital it is to make water accessible for resident’s need, industries and other commercial organizations. Since water demand is increasing day by day, the source of water becomes limited. To solve this problem, the design of new or improvement of existing water distribution network is obligatory in order to ensure the availability of sufficient amount of decent quality of water in accordance with the demand. Hence this study is based on the assessment of existing water distribution network in Putrajaya using EPANET 2.0 software and out of all the tools offered, EPANET turn out to be the most popular and convenient for effective design of complex pipe networks. The pipe network and junction network system is simulated to comprehend its behaviour with different inputs using EPANET 2.0. Simulation has been perform for hydraulic factors such as head, pressure and flow rate. The results achieved proved that the pressures at all junctions and the flows with their velocities at all pipes are practical enough to provide adequate water to the network of study area.